Educação do campo e participação: análise da produção do conhecimento dos quilombolas egressos do primeiro curso de Pedagogia do Campo/UFPB - Santos, Thatyanne Krause Lima Brito dos (2015)
This dissertation aims to analyze the production of knowledge of the quilombo graduates of the first field of the pedagogy course at UFPB through the category participation. Our specific objectives seek to discuss the participation category expressed in the monographs of the Maroons students; identify how popular education contributes to the educational process; verify participation emerging from the production of knowledge generated by the Maroons graduates and what perspectives theoretical and methodological addressed in the monographs of the Maroons young Community. From a methodological point of view, the research was based on bibliographic study is a qualitative and exploratory nature, taking account of the dialectical method. Data analysis technique used as content analysis. It could be observed that the formation of these subjects, previous to the university, made sure they possess a specific look both in popular culture, as in the struggle and resistance class oppression, ethnic and territorial in which they live. However, in the monographs it was found that the college gives them a systematization and reflection of social problems. From the concrete practice of their realities, prior to the course, the questions that resulted were later brought in his monograph. The immediate reality was being held. Subsidized by the critical theories, reflect on their practices were beyond immediate appearances, unveiled, discussed, studied critically, sought deeper on the topics questioning them, and from such reasons, returned to practice to try to transform it. Based on the foregoing we can consider that in all monographs was present critical participation through organicity provided by academic. Participatory processes analyzed in the monographs, subsidized by the People's Education, were strengthened by providing the face of the dominant hegemony.